Justice and the genesis of war - Welch, David 1960- (Cambridge studies in international relations, 1993)
Studies of the causes of wars generally presuppose a 'realist' account of motivation: when statesmen choose to wage war, they do so for purposes of self-preservation or self-aggrandizement. In this book, however, David Welch argues that humans are motivated by normative concerns, the pursuit of which may result in behaviour inconsistent with self-interest. He examines the effect of one particular type of normative motivation - the justice motive - in the outbreak of five Great Power wars: the Crimean war, the Franco-Prussian war, World War I, World War II, and the Falklands war. Realist theory would suggest that these wars would be among the least likely to be influenced by considerations other than power and interest, but the author demonstrates that the justice motive played an important role in the genesis of war, and that its neglect by theorists of international politics is a major oversight